Identifying the interdependence between South Africa's monetary policy and the stock market - Muroyiwa, Brian (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2011)
This study estimates the interdependence between South Africa"Ÿs monetary policy and stock market performance, utilising structural vector autoregression (SVAR) methodology. The study finds that a stock price shock which decrease stock prices by 100 basis points leads to 5 basis points decrease in interbank rate. A monetary policy shock that increases the interbank rate by l percent leads to decrease in real stock prices by 1 percent. This result for South Africa is similar to the result by Bjornland and Leteimo (2009) which earlier concluded that there was a high interdependence between interest rate setting and stock prices. However the magnitude of the relationship is relatively lower for South Africa compared to that of the United States of America (USA). The result of the current study is also very much consistent with the argument that the South African stock market is resource-based and so is influenced by external shocks, meaning monetary policy shock does not have as much impact on stock market in South Africa as in the USA. However the SARB may have to consider watching movements in stock prices so that booms in stock markets do not defeat central bank monetary policy thrusts. The stock price market is an essential source of information for monetary policy in South Africa.
Keywords: Monetary policy -- South Africa; Stock exchanges -- Law and legislation -- South Africa; Interest rates -- South Africa; Securities -- Prices -- South Africa